Light-enabled metal-free pinacol coupling by hydrazine. Issue 47 (22nd October 2019) - Qiu, Zihang; Pham, Hanh D. M.; Li, Jianbin; Li, Chen-Chen; Castillo-Pazos, Durbis J.; Khaliullin, Rustam Z.; Li, Chao-Jun
Abstract : A light-driven pinacol coupling protocol without any metals, but with N2 H4 as a clean non-metallic hydrogen-atom-transfer (HAT) reductant was described. Abstract : Efficient carbon–carbon bond formation is of great importance in modern organic synthetic chemistry. The pinacol coupling discovered over a century ago is still one of the most efficient coupling reactions to build the C–C bond in one step. However, traditional pinacol coupling often requires over-stoichiometric amounts of active metals as reductants, causing long-lasting metal waste issues and sustainability concerns. A great scientific challenge is to design a metal-free approach to the pinacol coupling reaction. Herein, we describe a light-driven pinacol coupling protocol without use of any metals, but with N2 H4, used as a clean non-metallic hydrogen-atom-transfer (HAT) reductant. In this transformation, only traceless non-toxic N2 and H2 gases were produced as by-products with a relatively broad aromatic ketone scope and good functional group tolerance. A combined experimental and computational investigation of the mechanism suggests that this novel pinacol coupling reaction proceeds via a HAT process between photo-excited ketone and N2 H4, instead of the common single-electron-transfer (SET) process for metal reductants.